Sobre a relação do direito com a moral em Kant : o conceito kantiano de direito como possibilidade moral ou como o reino do moralmente possível - Alan Ricardo Pereira (2020)
Starting from the problem of whether Kant's theory of law is independent from (or rather dependent) on his moral theory – practical philosophy – (a problem with which Kant himself often struggled), this work argues for the specificity of law in the realm of pure practical reason. In other words, this work argues that law depends on morals, but it does not depend on ethics. Such independence (of law from ethics), however, does not imply that the law cannot be (indirectly) incorporated into ethics. To argue that, this research is articulated around three systematically juxtaposed parts, the first of which appropriates concurrent opinions – on the problem of whether law is independent (chapter 1) or rather dependent on morals (chapter 2) – in order to conclude pointing out which interpretation best fits Kant's own thought: the specificity of law within practical philosophy, we argue (chapter 3). In the second part, we clarify (for there is considerable confusion regarding this matter) the principle of law in Kant's work (1781-1796) (chapter 4) and we establish its bordering relationship with morals also in the same period (chapter 5) – that is, before the Metaphysical Principles of the Doctrine of Law (1797) came to light, this being of course the work which contains the core of Kant's philosophy of law. This second part thus makes use of Kant's interpreters appropriations or receptions of his thought – we mean his contemporaries who, inspired by the critical philosophy, attempted to deduct law as much as possible in contiguity with the philosopher from Königsberg (chapter 6). The third part, in its turn, elaborates on three distinct moments of exposition to answer the question at stake. Within the first one, it is shown that law belongs to morals (chapter 7); within the second one, it is then shown that law and ethics are separated – despite the law being indirectly incorporated into ethics (chapter 8). Within the third one, in its turn, it is shown that law is circumscribed within the realm of the morally possible (chapter 9). This being about building a case for the understanding of law as a moral possibility or as the realm of the morally possible (using the basic notions of deontic logic), the aforementioned tripartite demonstration thus becomes a very powerful resource. In fact, starting from such demonstration, one can envision the following solution to our problem: if law belongs to morals (in a broad sense – everything that freedom makes possible), but has nothing to do with ethics (the doctrine of virtue, that is, the forum of conscience), then one could conclude thusly: one is authorized (in terms of it being permitted or licit) to do something (which is not circumscribed in the ethical/inner sphere) only if it is morally possible to do so – that is, only if such is possible in terms of external freedom (juridical freedom).